Perizinan Usaha Berbasis Resiko dan Dampaknya bagi Masa Depan Investasi di Indonesia - Miranti Angkareda (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Indonesian Goverment did so many changes in a way to ease and to grow the sentimen of investor which is good and can attract new company to born and growth in Indonesia. To increase investment and to speed up the growth of Economic also to improve a Good Governance system to led a better future. With the dealth of Peraturan Pemerintah No. 5 Tahun 2021 it talks about Execution License Bussiness Base on Risk, then Indonesian Governance has been launched OSS-RBA to ease make the license of bussiness. This study to acknowledge the plus and minus of license for bussiness base risk and the excution to online law single submission to push more investment also it triggred because of excecution license base risk for the better future of investment positivity. Then as long as I know I can conclude from the procedural it is very closely related and influental to the license of bussiness because in this way can give an ease to all enterpreneurs, however this impact could not happen if it’s written only in the books of law Undang-Undang which exist, not only to refers on normatively orders, but it should be consistanly, commited in the implementing the right rules.